PENGARUH CALLING TERHADAP KEPUASAN KERJA YANG DIMEDIASI ORGANIZATIONAL INSTRUMENTALITY DI RUMAH SAKIT JIWA ACEH - Ayu Safira; Murkhana Murkhana (Departemen Manajemen, 2020)
This study aims to analyze the effect of Calling on Job Satisfaction on nurses, to analyze the effect of Calling on Organizational Instrumentality on nurses at the Aceh Mental Hospital. The sample used in this study amounted to 135 respondents. Data collection equipment used in this study was a questionnaire. The sampling technique used is saturated sampling. The analytical method to determine the effect of all the variables involved is Hirerarchical Linear Modeling (HLM). Based on the results of the HLM analysis, indicating that Calling has a positive effect on Job Satisfaction, Calling has a positive effect on Organizational Instrumentality, Organizational instrumentality has a positive effect on job satisfaction, Organizational Instrumentality mediates the relationship of Calling on Job Satisfaction.